2020
DOI: 10.1002/fsn3.2068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microbial diversity and functional differences in different types of high‐temperature Daqu

Abstract: Bacterial communities that enrich in high‐temperature Daqu are important for the Chinese maotai‐flavor liquor brewing process. However, the bacterial communities in three different types of high‐temperature Daqu (white Daqu, black Daqu, and yellow Daqu) are still undercharacterized. In this study, the bacterial diversity of three different types of high‐temperature Daqu was investigated using Illumina MiSeq high‐throughput sequencing. The bacterial community of high‐temperature Daqu is mainly composed of therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 84 publications
2
57
3
Order By: Relevance
“… Du et al (2019) proved that both the raw materials and the environments acted as important sources for Daqu microbiota ( Du et al, 2019 ). Because of the relatively open processing environment and the barefoot stepping process by women, there might be some microbiota such as Staphylococcus originating from the environment or women’ feet in Daqu ( Wang et al, 2021 ). During maturation, it was gradually inhibited by Kroppenstedtia ( He et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Du et al (2019) proved that both the raw materials and the environments acted as important sources for Daqu microbiota ( Du et al, 2019 ). Because of the relatively open processing environment and the barefoot stepping process by women, there might be some microbiota such as Staphylococcus originating from the environment or women’ feet in Daqu ( Wang et al, 2021 ). During maturation, it was gradually inhibited by Kroppenstedtia ( He et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, fermentation plays an important role in the production of volatile flavors and critical secondary metabolites ( Zheng et al, 2011 ). Daqu , made of wheat, barley, pea, and/or corn, is the most common starter and adopted in all the famous Baijiu in China ( Wang et al, 2021 ). Daqu production needs a series of steps, including moistening, breaking, mixing shaping, spreading, incubating, and maturation ( Zheng et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…This complex solid-state fermentation process is repeated for seven cycles in an open and uncontrolled environment with multi-microorganisms ( Li et al, 2016 ; Du et al, 2019 ; Liu et al, 2019 ). These microorganisms have a major impact on fermentation yield and quality, mainly derived from HTD, a saccharifying starter, and raw material used in the brewing process of SFB ( Li et al, 2017 ; Yang et al, 2018 ; Wang Y. R. et al, 2021 ). HTD is composed of pea and barley along with wheat as primary raw materials and is made by shaping, piling, fermenting, and ripening under high temperature conditions (60–70°C) ( Li et al, 2016 , 2017 ; Fan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the different colors produced after browning, the HTD was mainly classified into three types (white HTD, black HTD, and yellow HTD). White HTD is mainly located at the top of the Daqu pile, accounting for 10–15% of total HTD; black HTD is mainly located in the middle of the Daqu pile, accounting for <1% of the total HTD; whereas yellow HTD is uniformly dispersed in the Daqu pile, accounting for 80–85% of the total HTD ( Gan et al, 2019 ; Wang Y. R. et al, 2021 ). During practical production, these three types of HTD are generally mixed and ground in a certain ratio for SFB fermentation ( Wang Y. R. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that the proportion of bacteria and fungi from Daqu was 81.5% and 79.2% respectively, in the fermented grain ( Wang P. et al, 2017 ). They not only affect the accumulation of enzymes in the fermentation process but also determine the final community composition ( Wang et al, 2021 ). Therefore, the Daqu microorganism group has a crucial effect on the quality formation of Nongxiang Baijiu.…”
Section: Introductionmentioning
confidence: 99%